Liquid-crystalline nanoarchitectures for tissue engineering - Baeckkyoung Sung; Min-Ho Kim (Beilstein Journal of Nanotechnology, 2018)
Hierarchical orders are found throughout all levels of biosystems, from simple biopolymers, subcellular organelles, single cells, and macroscopic tissues to bulky organs. Especially, biological tissues and cells have long been known to exhibit liquid crystal (LC) orders or their structural analogues. Inspired by those native architectures, there has recently been increased interest in research for engineering nanobiomaterials by incorporating LC templates and scaffolds. In this review, we introduce and correlate diverse LC nanoarchitectures with their biological functionalities, in the context of tissue engineering applications. In particular, the tissue-mimicking LC materials with different LC phases and the regenerative potential of hard and soft tissues are summarized. In addition, the multifaceted aspects of LC architectures for developing tissue-engineered products are envisaged. Lastly, a perspective on the opportunities and challenges for applying LC nanoarchitectures in tissue engineering fields is discussed.